Anti-inflammatory Effects of Traditional Chinese Medicines on Preclinical in vivo Models of Brain Ischemia-Reperfusion-Injury: Prospects for Neuroprotective Drug Discovery and Therapy - Peng, Tangming; Jiang, Yizhou; Farhan, Mohd; Lazarovici, Philip; Chen, Ligang; Zheng, Wenhua (Frontiers in Pharmacology, 2019)
Acquired brain ischemia-and reperfusion-injury (IRI), including both Ischemic stroke (IS) and Traumatic Brain injury (TBI), is one of the most common causes of disability and death in adults and represents a major burden in both western and developing countries worldwide. China’s clinical neurological therapeutic experience in the use of traditional Chinese medicines (TCMs), including TCM-derived active compounds, Chinese herbs, TCM formulations and decoction, in brain IRI diseases indicated a trend of significant improvement in patients’ neurological deficits, calling for blind, placebo-controlled and randomized clinical trials with careful meta-analysis evaluation. There are many TCMs in use for brain IRI therapy in China with significant therapeutic effects in preclinical studies using different brain IRI-animal. The basic hypothesis in this field claims that in order to avoid the toxicity and side effects of the complex TCM formulas, individual isolated and identified compounds that exhibited neuroprotective properties could be used as lead compounds for the development of novel drugs. China’s efforts in promoting TCMs have contributed to an explosive growth of the preclinical research dedicated to the isolation and identification of TCM-derived neuroprotective lead compounds. Tanshinone, is a typical example of TCM-derived lead compounds conferring neuroprotection toward IRI in animals with brain middle cerebral artery occlusion (MCAO) or TBI models. Recent reports show the significance of the inflammatory response accompanying brain IRI. This response appears to contribute to both primary and secondary ischemic pathology, and therefore anti-inflammatory strategies have become popular by targeting pro-inflammatory and anti-inflammatory cytokines, other inflammatory mediators, reactive oxygen species, nitric oxide, and several transcriptional factors. Here, we review recent selected studies and discuss further considerations for critical reevaluation of the neuroprotection hypothesis of TCMs in IRI therapy. Moreover, we will emphasize several TCM’s mechanisms of action and attempt to address the most promising compounds and the obstacles to be overcome before they will enter the clinic for IRI therapy. We hope that this review will further help in investigations of neuroprotective effects of novel molecular entities isolated from Chinese herbal medicines and will stimulate performance of clinical trials of Chinese herbal medicine-derived drugs in IRI patients.